TRANSITIONAL STUDY OF SUSTAINABLE BEHAVIOUR IN REDUCING IMAGINARY COSTS / ARTICLE REVIEW - Nabeel Farhan Hamdan (Scholars Digest Publishing, 2023)
Today's business environment is witnessing a great competition between economic organizations or units, as obtaining customer satisfaction and their loyalty and achieving sustainability requirements has become a preoccupation of all successful economic units that seek to sustain and ensure their success successfully in the business environment, so these units have taken it upon themselves to apply many technologies and means That has information about what customers ’requirements and desires are, and these means are technologies that have received great attention in the application aspect according to the concept of new sustainability. Among these technologies or tools is the tool of spreading the sustainable quality function and the targeted cost of sustainability that transforms the requirements of customers and their desires according to the technology of our time, Where the research shows the concept of sustainability, its dimensions and the goals of its application, as well as the determinants facing the application of sustainability, and sustainability technologies as well as addressing the reduction of costs in terms of concept, definition and discount mechanism.
Keywords: sustainability, cost reduction, sustainable quality function technology, Sustainable quality house , sustainable balanced score card.